PENAMBAHAN BIT (BETA VULGARIS L.) SEBAGAI PEWARNA ALAMI TERHADAP DAYA TERIMA DAN KANDUNGAN ZAT GIZI KERUPUK MERAH - Siti hairunnisa pohan; Evawany Y Aritonang; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Red crackers is a lots of food consumed by the people of Indonesia as a complement to eat fried rice, fried noodle and others. Substance dye used in the manufacture of red crackers are often using the dye that banned such as rhodamine B. Beetroot Essence can be used as a natural dye on manufacture of the red crackers. This is an experimental research with two treatment, where is the treatment given is : the addition of beetroot essence 25 % (P1) and the addition of beetroot essence 50 % (P2). Data collection method conducted with organoleptic test by 30 not trained panelists, they are students from Faculty of Public Health University of Sumatera Utara. Data analysis of the organoleptic test result it was descriptive qualitative percentage. The result of this experimental showed that acceptability for crackers with the addition of beetroot essence 50 % (P2) more preferred by the panelists in terms of aroma, color, flavor and texture, with a total score of each 90 (74,9 %), 98 (81,6 %), 91 (75,7 %), dan 95 (79,1 %). The laboratory test result showed the addition of beetroot essence 50 % contains of fiber higher 8,5 %, contains of protein higher 0,8750 % and contains of vitamin C higher 3,3 % . The addition of beetroot essence 25 % contains of fat higher 54,1 % and contains of moisture higher 0,24 %. Laboratory test result for ash, the addition of beetroot essence 25 % and 50 % contains the same result is 0,33 %. Efforts should be made to introduce more crackers with addition of beetroot essence as a natural dye that is safe to the public. Keywords : Crackers, Beetroot Essence, Natural Dye